The impact of caloric information on college student's fast food purchasing intentions - Zigmont, Victoria A; Bulmer, Sandra Minor (American journal of health education, 2015)
Background: Fast food establishments are available on many college campuses and, as a result, many students consume foods that are high in calories and contribute to unhealthy weight gain. Purpose: This study measured college students' knowledge of the calorie content for fast food items and whether the provision of calorie information for those foods influenced their future purchasing intentions. Method: Randomly selected undergraduate college students (N = 201) completed an online survey that measured baseline knowledge of calorie content for a fast food item and intention to purchase that item in the future. After provision of accurate calorie information, students were posttested for intention to purchase that item in the future. Results: The majority of students underestimated calorie content for fast food items. After receiving accurate calorie information, those who initially underestimated calorie content were significantly more likely to change their intention to purchase that food item in the future. Discussion: Many college students are interested in avoiding high-calorie fast food items but are uninformed about calorie content. Translation to Health Education Practice: Colleges should provide calorie information for fast food items at the point of purchase so that students can make informed decisions that will promote their health. © 2015, Copyright © SHAPE America.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-184-250-213-713 tex.type: [object Object]
Keywords: dept.hhs; dept.pch